Induced Pluripotent Stem Cells in Congenital Long QT Syndrome: Research Progress and Clinical Applications - Qing Li; Yi-Fei Wang; Bin Wang; Ting-Ting Lv; Ping Zhang (Reviews in Cardiovascular Medicine)
Congenital long QT syndrome (LQTS) is a potentially life-threatening hereditary arrhythmia characterized by a prolonged QT interval on electrocardiogram (ECG) due to delayed ventricular repolarization. This condition predisposes individuals to severe arrhythmic events, including ventricular tachycardia and sudden cardiac death. Traditional approaches to LQTS research and treatment are limited by an incomplete understanding of its gene-specific pathophysiology, variable clinical presentation, and the challenges associated with developing effective, personalized therapies. Recent advances in human induced pluripotent stem cell (iPSC) technology have opened new avenues for elucidating LQTS mechanisms and testing therapeutic strategies. By generating cardiomyocytes from patient-specific iPSCs (iPSC-CMs), it is now possible to recreate the patient’s genetic context and study LQTS in a controlled environment. This comprehensive review describes how iPSC technology deepens our understanding of LQTS and accelerates the development of tailored treatments, as well as ongoing challenges such as incomplete cell maturation and cellular heterogeneity.